Scheduling of a textile production line integrating PV generation using a genetic algorithm. (December 2020) - Ramos, Carlos; Barreto, Rúben; Mota, Bruno; Gomes, Luís; Faria, Pedro; Vale, Zita
Abstract: Considering the technological advances of the industrial sector today, it appears that the management of energy resources has become increasingly prominent. Thus, to make this management more efficient, it is necessary to take into account the production planning and scheduling concept, since it allows influencing the scheduling of production at the level of cost and efficiency. Thus, the objective of this paper is to present a methodology that allows making the best possible scheduling of a textile production line to optimize it. This optimization is elaborated with the help of genetic algorithms, and, as it can be verified in this paper, it is possible to make an optimization of the production line at the level of energy cost or the level of energy consumption or optimization of both. Thus, the case study of this paper is based on a textile production line that produces a variety of products through three machines capable of performing numerous tasks, which can be done on more than one machine. Likewise, this production line enjoys photovoltaic production. This paper presents several case studies that allow for highlighting the impact of the methodology covered in the respective production line, where it is illustrated through different graphics.